All the Colors of the Rainbow: Diversification of Flower Color and Intraspecific Color Variation in the Genus Iris - Roguz, Katarzyna; Gallagher, M. Kate; Senden, Esther; Bar-Lev, Yamit; Lebel, Merav; Heliczer, Roni; Sapir, Yuval (Frontiers in Plant Science, 2020)
Floral colour plays a key role as visual signalling and is therefore of great importance in shaping plant-pollinator interactions. Iris (Iridaceae), a genus comprising over 300 species and named after the Greek goddess of the colourful rainbow, is famous for its dazzling palette of flower colours and patterns, which vary considerably both within and among species. Despite the large variation of flower colour in Iris, little is known about the phylogenetic and ecological contexts of floral colour. Here, we seek to resolve the evolution of flower colour in the genus Iris in a macroevolutionary framework. We used a phylogenetic analysis to reconstruct the ancestral state of flower colour and other pollination-related traits (e.g., the presence of nectar and mating system), and also tracked the evolution of colour variation. We further explored weather floral trait transitions are better explained by environmental or pollinator-mediated selection. Our study revealed that the most recent common ancestor likely had monomorphic, purple flowers, with a crest and a spot on the fall. The flowers were likely insect-pollinated, nectar-rewarding, and self-compatible. The diversity of floral traits we see in modern irises, likely represents a trade-off between conflicting selection pressures. Whether shifts in these flower traits result from abiotic or biotic selective agents or are maintained by neutral processes without any selection remains an open question. Our analysis serves as a starting point for future work exploring the genetic and physiological mechanisms controlling flower colouration in the most colour-diverse genus Iris.